Criminal Responsibility of Notary as a Consequence of Producing an Authentic Deed Judging from the Notarial Official Authority Within the Law on Notary Profession - Agustining, Agustining (LITERATUS, 2024)
A notary is a public official who works based on the authority according to the Notary Law (UUJN). The authority of a notary is regulated, among other things, in Article 15 (1) of the UUJN. A notary has the authoritymake authentic deeds regarding all acts, agreements, and determinations required by laws and regulations. The problem is that notaries as public officials generally work in the realm of civil legal acts. However, in carrying out duties mandated by law and of a civil nature, in public office notaries can be held criminally responsible in criminal courts, either as witnesses or even as suspects and convicts due to the deeds they make. The conflicting situation of das sollen versus das sein requires a ratio legis. For this reason, this research was conducted using a legal research method, with complementary support in the form of empirical data, the results of observations on data from 111 notaries in North Sumatra who were involved in casescriminal in that area. The study found that the presence of a notary in providing criminal responsibility is possible, with the approval of the Regional Notary Honorary Council (MKNW), as happened in 2023. Approval from the MKNW is given after being requested by Law Enforcement Officers (APH). The authority to provide approval from the MKNW is in order to carry out the mandate of Article 66 (1) of Law No. 2 of 2014 in conjunction with the Minister of Law and Human Rights RegulationNo. 17 of 2021; among others, to carry out notary guidance through granting or refusing approval requested by APH to allow notaries to be held criminally responsible in the investigation, prosecution and trial process. However, the authority to grant MKNW permits still seems less able to reduce the number of indications of notary involvement in a criminal act related to a deed made by a notary.